Peningkatan Transparansi Keuangan: Implementasi Sistem Informasi Akuntansi Berbasis Cloud - Komala, Rina; Fahry, Fahry; Elisa, Nopa (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study explores the impact of implementing a cloud-based accounting information system on financial transparency in the tourism sector of Lombok Island. A mixed-methods approach was employed, including quantitative analysis of 120 businesses and qualitative interviews with 25 informants. The results revealed that 90% of respondents reported improved financial transparency after adopting cloud systems, highlighting operational efficiency, reporting accuracy, and ease of data access. However, challenges such as implementation costs, limited internet infrastructure, and a lack of local expertise remain significant barriers. This study recommends local training, subsidized implementation costs, and improved infrastructure to accelerate adoption. Cloud systems are expected to enhance not only financial transparency but also the competitiveness of small and medium enterprises in Lombok's tourism sector. This research contributes to developing relevant financial technology strategies to support digital transformation in Indonesia's tourism industry.